KOMPARASI TAFSIR AL-MANAR DAN TAFSIR AL-MARAGHI STUDI CORAK ADABI IJTIMA’I DALAM MERESPONS MODERNITAS - Muhammad Nur Hidayat; Asep Ahmad Fathurrohman; Edi Komarudin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
This study conducts a critical-comparative analysis of Tafsir Al-Manar and Tafsir Al-Maraghi, both of which share the Adabi Ijtima'i (Social-Cultural) style, to uncover the root cause of their differences ('illat al-ikhtilaf) in responding to modernity. Using a qualitative approach with the muqāranah (comparative) method and content analysis, this research examines methodological aspects and substantive interpretations of three key verses: Q.S. Yunus [10]: 100 (reason), Q.S. An-Nisa' [4]: 59 (politics), and Q.S. An-Nisa' [4]: 34 (family). The findings reveal that despite sharing a basic style, the two commentaries exhibit systematic divergence. Al-Manar, dominated by bil ra'yi (70%) and an Islahi-Siyasi (Reformist-Political) tendency, produces transformative and polemical responses. In contrast, Al-Maraghi, dominated by bil ma'tsur (60%) and a Tarbawi-Ilmi (Educational-Scientific) tendency, produces stabilizing-educative responses. This study concludes that the primary 'illat al-ikhtilaf lies in the interaction between the Tsaqofah al-Mufassirin (the intellectual-institutional framework of the exegetes) and their historical context. Al-Manar, a product of Salafi-Activist Tsaqofah in the Early Modern era, advocates for transformative-political tajdid (renewal). Meanwhile, Al-Maraghi, a product of Azhari-Institutional Tsaqofah in the Middle Modern era, advocates for stabilizing-educative tajdid. Thus, this study not only maps the differences but also contributes to the science of tafsir by introducing Tsaqofah al-Mufassirin as an analytical framework and two models of renewal (tajdid) born from the Adabi Ijtima'i style.